Implementasi Load Balancing Per Connection Classifier pada Infrastruktur Jaringan Yayasan TPQ Al-Falah - Azmi, M. Abid Ulil; Rahman, Miftahur; Daryanto; Ahmad Fawaiz (Fakultas Sains dan Teknologi, Universitas Ibrahimy, 2026)
The need for a fast, stable and reliable internet connection is very important, including in educational institutions such as TPQ AL-FALAH, which functions to manage the administration system, as well as stream events directly via YouTube. However, the use of one internet line is often unable to provide stability, so a solution is needed in the form of combining two ISP lines using load balancing techniques. This research implements the Per Connection Classifier (PCC) method on a Mikrotik device to combine two internet lines from different ISPs, namely PT Global Media Data Prima and the Orbit Star 2 modem. This method allows for even network distribution between available connections. This research also analyzes Quality of Service (QoS). Testing is carried out based on four main parameters, namely delay, jitter, packet loss and throughput. The analysis results show that load balancing using the PCC method in scenario 3 is the best result, namely when both ISPs are active simultaneously with a delay value of 0.8 ms, jitter 0.01 ms, packet loss 0.11%, and throughput 9038 kbps, based on the TIPHON standard category, then the QoS analysis parameter results for scenario 3 are all parameters in the excellent or very good category. Thus, this load balancing system has proven effective in improving the performance and reliability of the internet network in the TPQ AL-FALAH work environment.